Effects of Particle Size of Rice on Resistant Starch and SCFA of the Digesta in Caecostomised Pigs - Y. Marsono; David L. Topping (Indonesian Food and Nutrition Progress, 1999)
A study on the relation between particle size and resistant starch (RS) has been conducted in pigs. The objectives of the study was to investigate the effects of particle size of rice (whole rice and rice flour) on the starch escaping digestion and volatile fatty acids (VFA) concentration in the large bowel of pigs fitted with a caecal cannula. Four pigs were caecostomised and given 4 diet different in particle size and NSP content e.i. Whole brown rice (WB), fine brown rice (FB), whole white rice (WW) and fine white rice (FW) for 8 days. There was a washed-out period of 6 days between changes of diet. Caccal content was taken every 2 hour (2-16 hours and 24 hours after feeding) by withdrawal through a plastic tube. The di gesta were analyzed for starch (RS) and VFA. it was found that concentrations of starch in caecal contents was the same when the animals fed cooked fine white and or fine brown rice diets. The caecal starch concentrations in animals fed the fine product varied from 15 to 44% of the values in animals fed the whole product, or brown rice and 18% to 45% for white rice. The presence of NSP was rather less important even though fibre is known to inhibit starch digestion. Differences in the particle size of rice did not affect concentration of the total VFA in the caecal contents. Small differences were found in the molar ratios of the major VFA with the butyrate being highest when pigs fed whole brown rice and lowest when the animals fed whole white rice.